Whole-genome sequencing and metagenomics reveal diversity and prevalence of Listeria spp. from soil in the Nantahala National Forest - Jia Wang; Claire N. Schamp; Lauren K. Hudson; Harleen K. Chaggar; Daniel W. Bryan; Katie N. Garman; Mark Radosevich; Thomas G. Denes (Microbiology Spectrum)
ABSTRACT Listeria spp. are widely distributed environmental bacteria associated with human foodborne illness. The ability to detect and characterize Listeria strains in the natural environment will contribute to improved understanding of transmission routes of contamination. The current standard for surveillance and outbreak source attribution is whole-genome sequencing (WGS) of Listeria monocytogenes clinical isolates. Recently, metagenomic sequencing has also been explored as a tool for the detection of Listeria spp. in environmental samples. This study evaluated soil samples from four locations across altitudes ranging from 1,500 to 4,500 ft in the Nantahala National Forest in North Carolina, USA. Forty-two Listeria isolates were cultured and sequenced, and 12 metagenomes of soil bacterial communities were generated. These isolates comprised 14 distinct strains from five species, including Listeria cossartiae subsp. cayugensis (n = 8; n represents the number of distinct strains), L. monocytogenes (n = 3), “Listeria swaminathanii” (Lsw) (n = 1), Listeria marthii (n = 1), and Listeria booriae (n = 1). Most strains (n = 13) were isolated from lower altitudes (1,500 or 2,500 ft), while the L. swaminathanii strain was isolated from both higher (4,500 ft) and lower (1,500 ft) altitudes. Metagenomic analysis of soil described a reduction in both bacterial community diversity and relative abundance of Listeria spp. as the altitude increased. Soil pH and cation exchange capacity were positively correlated (P < 0.05) with the abundance of Listeria spp. as detected by metagenomics. By integrating culture-independent metagenomics with culture-based WGS, this study advances current knowledge regarding distribution of Listeria spp. in the natural environment and suggests the potential for future use of culture-independent methods in tracking the transmission of foodborne pathogens.IMPORTANCEAs a foodborne pathogen, Listeria continues to cause numerous illnesses in humans and animals. Studying the diversity and distribution of Listeria in soil is crucial for understanding potential sources of contamination and developing effective strategies to prevent foodborne outbreaks of listeriosis. Additionally, examining the ecological niches and survival mechanisms of Listeria in natural habitats provides insights into its persistence and adaptability, informing risk assessments and public health interventions. This research contributes to a broader understanding of microbial ecology and the factors influencing foodborne pathogen emergence, ultimately enhancing food safety and protecting public health. Moreover, using a metagenomic approach provides a detailed understanding of the soil microbial ecosystems, leading to more effective monitoring and control of foodborne pathogens. This study also highlights the potential for integrating metagenomics into routine surveillance systems for food safety in the near future.